Dobrze odrobiona lekcja – czyli o konstruktywnym wykorzystaniu przez środowisko lokalne doświadczeń oraz badań naukowych dla rozwoju edukacji - Jarosz, Ewa (Pedagogika Społeczna Nova, 2021)
The paper presents initiative of making a diagnosis of the situation in education during pandemic time and the fruits of if which are the diagnostic picture of the environmental needs and projects of changes in education in a local environment – one of the parishes in the Silesia district. The paper describes the process of the realization of social engaged scientific research in a local environment, which is based on the influence of specific trauma for the readiness to undertake scientific reflection on the situation in education and the needs in this area but also based on the willingness of making changes in the reality of the local education. So, the article is an attempt to present possibilities to use difficult experiences of the online education forced by the pandemic reality for making constructive changes in a local context. It presents tendencies and phenomena of changes that can be observed in many local environments and educational institutions as positive consequences of the difficult situation of the pandemic education. Moreover, it is an attempt of presenting a good example of the partner collabora- tion social-local and scientific environments, directed for changing the environment and the reality of the education into the ones that are the better contexts of individual and over individual development. So it may be said that the paper is a narration about the possibility of social influence of researchers, about socially engaged research. The paper presents the both the beginnings, the process and some results of the diagnosis but also worked out in a dialog with local authorities recommendations and proposals of changes.